Specifics of Left Ventricular Hypertrophy and Characteristic of Phenotypic Variants in Patients with Hypertrophic Cardiomyopathy - G. I. Ignatenko; G. G. Taradin; T. E. Kugler (Архивъ внутренней медицины)
Hypertrophic cardiomyopathy is characterized by genetic and phenotypic heterogeneity which manifests in different variants of localization and extent of myocardial hypertrophy.Aim: to evaluate specifics of left ventricular hypertrophy, the prevalence and characteristics of clinical and instrumental features of phenotypic variants of hypertrophic cardiomyopathy.Materials and methods. The study includes 295 patients with hypertrophic cardiomyopathy aged 18 to 88 years (60.3±13.4 years), 183 men (62 %), and women 112 (38 %). The diagnosis of which was established by 2D echocardiography. The severity, localization and extent of myocardial hypertrophy, the maximum thickness of the hypertrophied segment, left ventricular myocardial mass, left ventricular myocardial mass index, the presence and severity of mid-ventricular and left ventricular outflow tract obstruction were evaluated. Depending on the predominant localization and extent of hypertrophy, patients were divided into 8 groups according to the recommendations for hypertrophic cardiomyopathy of the Ministry of Health of the Russian Federation. The analysis and comparison of the obtained results are carried out.Results. The average duration of the disease is 10.5±7.52 years. The mean values of the body mass index in patients — 28.2±2.82 kg/m2. The phenotype with basal hypertrophy of the septum (n=130, 44.1 %), group 1 was most often noted. In 47 (15.9 %) patients, hypertrophy of the septum of “reverse curve” (2 group) was detected, in 41 (13.9 %) — “neutral septum” (3 group), in 36 (12.2 %) — symmetrical hypertrophy of the left ventricle (8 group), 11 (3.7 %) of patients had combined hypertrophy of the septum and other parts of the left or right ventricle (4 group) and the free left ventricular wall (7 group), in 10 (3.4 %) — middle ventricular hypertrophy of the left ventricle (6 group) and in 9 (3.1 %) — apical hypertrophy (5 group). The highest value of the maximum thickness of the myocardium was noted in patients of the 6th group 19.3 (1920.4 mm). Mid-ventricular obstruction was detected in group 6 (90 %), left ventricular outflow tract obstruction was more often registered in groups 4 and 8 (81.8 % and 77.8 %), and less often in group 5 (22.2 %) (p <0.01). In group 7, there were no cases of rest obstruction of left ventricular outflow tract. The maximum values of myocardial mass and left ventricular myocardial mass index were noted in group 8 — 402 (356-439) g and 195 (173218) g/m2, respectively (p <0.01).Conclusion. Echocardiography is an informative tool for assessing the presence, severity myocardial hypertrophy and determination of the phenotypic variant of hypertrophic cardiomyopathy. Variants of septal hypertrophy are most commonly registered one, among which the most frequent is the phenotype of basal septal hypertrophy. Each phenotype of hypertrophic expression is characterized by its echocardiographic parameters.